2014
DOI: 10.1089/end.2013.0475
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Radical Prostatectomy Demonstrates Less Morbidity Than Open Radical Prostatectomy: An Analysis of the American College of Surgeons-National Surgical Quality Improvement Program Database with a Focus on Surgical Trainee Involvement

Abstract: The large sample size, standardized data definitions, and quality control measures of the ACS-NSQIP database allow for in-depth analysis of subtle, but significant differences in outcomes between groups. Trainee involvement in LRP appears safe to patients. However, the increased morbidity in ORP involving trainees may be mitigated by awareness, simulation laboratories, and standardized competency assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The growing literature on resident involvement in urologic procedures suggests that their integration can be done safely and without significantly adversely affecting patient outcomes. Our findings on radical prostatectomies are consistent with prior studies on open 21 and laparoscopic 15 prostatectomies that demonstrated resident involvement in those surgeries to be safe, with equivalent morbidity, although with increased operative time. Kern and colleagues also utilized the NSQIP database to examine the impact of training level on outcomes of partial nephrectomies from 2005 to 2010 and showed increased operative time, overall morbidity, surgical site infections, bleeding, sepsis, and septic shock when residents at any level were involved.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The growing literature on resident involvement in urologic procedures suggests that their integration can be done safely and without significantly adversely affecting patient outcomes. Our findings on radical prostatectomies are consistent with prior studies on open 21 and laparoscopic 15 prostatectomies that demonstrated resident involvement in those surgeries to be safe, with equivalent morbidity, although with increased operative time. Kern and colleagues also utilized the NSQIP database to examine the impact of training level on outcomes of partial nephrectomies from 2005 to 2010 and showed increased operative time, overall morbidity, surgical site infections, bleeding, sepsis, and septic shock when residents at any level were involved.…”
Section: Discussionsupporting
confidence: 89%
“…[10][11][12][13][14][15] In an increasingly cost-conscious medical culture, delivering high quality care is of utmost importance, translating in greater involvement of attending surgeons and less resident independence. 12 Moreover, surgical resident education is increasingly challenging due to expense, 19 work hour limitations 20 and an ever-increasing array of minimally-invasive surgical options to complement open surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in a large cohort that trainee involvement with both LP and ORP appears to be related to a significantly increased risk of perioperative morbidity, and this risk was found to be significantly higher in the context of ORP . Another large study of trainee involvement in ORP found that trainee involvement was associated with longer operative time, but that there was shorter length of hospital stay in the academic institutions.…”
Section: Discussionmentioning
confidence: 98%
“…Following the learning curve with ORP, a well‐established relationship has been shown to exist between surgeon volume and patient outcomes, including perioperative morbidity, quality of life outcomes and oncological outcomes . The effect of urology trainees on patient outcomes following ORP has also been shown, but to date these outcomes have only included post‐operative complications and length of hospital stay . There has been no published literature addressing the effect of urology trainee involvement in ORP and long‐term oncological outcomes when the trainee is supervised by a high‐volume or low‐volume surgeon.…”
Section: Introductionmentioning
confidence: 99%